Analisis Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Poliklinik Bedah Mulut - Mashuda, Mashuda; Aflanie, Iwan; Shadiqi, Muhammad Abdan; A, Izaak Zoelkarnain; Nugroho, Adi (Universitas Pahlawan Tuanku Tambusai, 2024)
Utilization of health services is an important aspect in developing health status. Based on data obtained from the utilization figures for specialist oral surgery polyclinics at RSGM Gusti Hasan Aman in the last 4 years, there have been fluctuations in the number of referrals to specialist oral surgery polyclinics and the number of patients visiting. It turns out that not all patients who visit the oral surgery clinic utilize the services at the polyclinic. Service utilization is related to various factors including perceptions of health and illness, health status, income, insurance membership, and availability of infrastructure. To determine the relationship between perceptions of health and illness, dental and oral health status (DMF-T), income, insurance membership, and availability of infrastructure and utilization of specialist oral surgery polyclinic services at RSGM Gusti Hasan Aman. This research uses an analytical observational method with a cross-sectional design. The research subjects consisted of 97 patients from the oral surgery clinic at RSGM Gusti Hasan Aman. Data analysis uses descriptive analysis, statistical analysis with the Chi square test and multiple logistic regression analysis. The results of analysis using Chi square show the p value of the variables perception of health and illness (p= 0.005), dental and oral health status (DMF-T) (p= 0.207), income (p= 0.170), insurance membership (p= 0.003), and availability of infrastructure (p= 0.000). The results of analysis using multiple logistic regression show the p value and Exp B of the health-sickness perception variable (p= 0.033, Exp B= 5.925), the dental and oral health status variable (DMF-T) (p= 0.068, Exp B= 4.225), income variable (p= 0.015, Exp B= 2.013), insurance membership variable (p= 0.005, Exp B= 14.111) and infrastructure availability variable (p= 0.000, Exp B= 18.534). There is a significant relationship between perceptions of health and illness, insurance membership, availability of oral surgery polyclinic infrastructure at RSGM Gusti Hasan Aman. There is no significant relationship between the dental and oral health status variable (DMF-T) and the income of the oral surgery clinic at RSGM Gusti Hasan Aman. The most dominant variable is the availability of infrastructure